2019
DOI: 10.21276/ap.2019.8.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Original article Comparative phytochemical screening, elemental content and chromatographic evaluation for detection and quantification of polyphenolic compounds for strong antioxidant activity of various extracts of Abutilon indicum (Link) Sweet leaves

Abstract: Abutilon indicum (Link) Sweet (AI) belongs to family Malvaceae. Traditionally, the plant was reported as healer for many ailments and other medicinal values such as leaves are effective against ulcer, laxative, expectorant, diuretic, astringent, analgesic, anti-inflammatory, anthelmintic, demulcent and aphrodisiac. Though, the plant is distributed in tropical and subtropical area, but is became threatened in Karnataka, India due to its habitat lost and over exploitation. The present experiment was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Recent studies have revealed the cytoprotective efficacy of bioactive compounds from traditional medicinal plant extracts ( Song et al, 2019 , Dhanasekaran et al, 2012 ). The phenolic compounds found in Abutilon indicum are known as powerful chain-breaking antioxidants ( Das et al, 2019 ). Polyphenols are the major phytochemical constituents reported in Abutilon indicum that scavenge free radicals due to its hydroxyl group and may directly contribute to its antioxidative functions ( Tlili and Sarikurkcu, 2020 , Abcha et al, 2019 , Bendary et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the cytoprotective efficacy of bioactive compounds from traditional medicinal plant extracts ( Song et al, 2019 , Dhanasekaran et al, 2012 ). The phenolic compounds found in Abutilon indicum are known as powerful chain-breaking antioxidants ( Das et al, 2019 ). Polyphenols are the major phytochemical constituents reported in Abutilon indicum that scavenge free radicals due to its hydroxyl group and may directly contribute to its antioxidative functions ( Tlili and Sarikurkcu, 2020 , Abcha et al, 2019 , Bendary et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…By now, anticancer, antiproliferative, anticholinesterase, antityrosinase, antioxidant, and other biological activities of numerous medicinal and aromatic plants (MAPs) and secondary metabolites isolated from MAPs were analysed in our laboratory (Akgunlu et al, 2016;Sekeroglu et al, 2017;Gezici et al, 2017;Belkhodja et al, 2017;Karik et al, 2018;Gundogdu et al, 2018;Senol et al, 2018;Gezici, 2018;Das et al, 2019;Shida et al, 2019;Gezici and Sekeroglu, 2019a;Gezici and Sekeroglu, 2019b;Gezici, 2019a;Gezici 2019b;Gezici, 2019, Sekeroglu et al, 2019 in press). Take into consideration our ongoing projects, evaluation cancer protective potentials against human cancer cells, investigating neuroprotective activities through enzyme inhibitions on acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and TYR (tyrosinase) enzymes, along with determination of antioxidant capacities of extracts obtained from red hulls, kernels and oleo-gum resins of Pistachio (P. vera L.) are the main objectives of the presented research.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the phenolic compounds present in A. hirtum may play a critical role as antioxidants, which are considered strong chain breaker agents as suggested by Ref. [ 68 ]. This may explain the previous results in the current study and confirm the success of using the plant for medicinal purposes, with the need to adjust the therapeutic dose.…”
Section: Discussionmentioning
confidence: 99%